ASSESSMENT OF THE EFFECT OF NEURAXIAL BLOCKADES ON EXTERNAL RESPIRATORY FUNCTION IN WOMEN WITH COMMUNITY-ACQUIRED PNEUMONIA AND RESPIRATORY FAILURE DURING ABDOMINAL DELIVERY (World Bulletin of Public Health, 2024)
Current anaesthesia guidelines indicate that general anaesthesia in patients with pneumonia, especially in pregnant women, is considered to increase the risk of anaesthetic complications and maternal mortality, and should therefore be avoided if possible [1,2,5]. However, a review of the literature revealed that according to data on maternal mortality in the UK, aspiration is the main cause of perioperative mortality during induction, aspiration pneumonitis, hemodynamic collapse and subsequent resuscitation failure. At the same time, in the United States, cases of mortality at the stage of induction of general anesthesia were not recorded